THE INFLUENCE OF NET PROFIT, FREE CASH FLOW, NET WORKING CAPITAL, FUNDING AND PROFITABILITY ON DIVIDEND POLICY IN FOOD AND BEVERAGE COMPANIES FOR THE 2019-2022 PERIOD - Yois Nelsari Malau; Cut Shafira Andini; Angelicca; Wenny Anggeresia Ginting (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to prove and examine the influence of net profit, free cash flow, net working capital, funding and profitability on dividend policy in food and beverage companies listed on the Indonesia Stock Exchange (BEI) in the period 2019 - 2022. This research uses a population of 84 food and beverage companies listed on the Indonesia Stock Exchange in 2019 - 2022. By using purposive sampling techniques, the research samples obtained were 11 companies which were multiplied over 4 years until the number to be used was 44 samples. The results of research using the F test show that the net profit variable, free cash flow variable, net working capital variable, funding variable and profitability variable simultaneously influence dividend policy. The results of the T test show that partially the net profit variable, free cash flow variable, funding variable and profitability variable have an influence and significance on dividend policy. Meanwhile, partially for net working capital there is no influence on dividend policy